Good Mechanism Corporate Governance and Size Company to Financial Performance in the Company Subsector Banks That Registered in Exchange Effect Indonesia Year 2018-2022 (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study was conducted on banks sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022 with the aim of testing and determining the effect of Good Corporate Governance Mechanisms (board of commissioners, board of directors, audit committee, institutional ownership) and Company Size on Financial Performance. The sampling technique used is the purposive sampling method where there are 26 companies x 5 years = 130. The analysis method used in this study is multiple linear regression analysis. Then the determination coefficient analysis is also used to see the magnitude of the variable contribution. Based on the results of the determination coefficient research in this study, it shows that the board of commissioners obtained a value of 0.046 <0.05, the board of directors 0.000 <0.05, institutional ownership 0.000 <0.05, and company size 0.003 <0.05, this shows that the board of commissioners, board of directors, institutional ownership and company size have an effect on financial performance. While the audit committee does not affect financial performance because its value is 0.942> 0.05.